Synthesis of Fe Nanoparticles via One-Step Reduction Method. Issue 12 (December 2016) - Ping, Hu; Lu, Kang; Jun, Yang; Fan, Yang; Kuaishe, Wang; Jinjing, Du; Zhanlin, Yang; Weicheng, Cao; Dongxin, Liu
Abstract: Fe nanoparticles were synthesized via a novel one-step reduction method. The excessive citric acid helps to obtain pure and high crystallinity α -Fe at the appropriate temperature (620 o C). The Fe nanoparticles were characterized by the X-ray diffraction, transmission electron microscopy (TEM) and vibrating sample magnetometer (VSM). The morphological characterization indicates that the Fe nanoparticles present spherical shape with diameter of 30 nm. The magnetization hysteresis loops reveal the high saturation magnetization ( M s =198.97 A·m 2 /kg) and the good ferromagnetic behavior of the magnetic materials. The one-step reduction method for nanoparticles synthesis has the advantages of controllable, short process, large-scale production, and will be an important method of producing nanoparticles